1999
DOI: 10.1093/humrep/14.4.946
|View full text |Cite
|
Sign up to set email alerts
|

Klinefelter's syndrome in the male infertility clinic

Abstract: The clinical features of patients with Klinefelter's syndrome attending a male infertility clinic have been investigated in order to consider their assisted reproduction treatment options. Over 12 years, a total of 148 patients with sterility due to azoospermia had Klinefelter's syndrome. Eight patients were shown by fluorescence in-situ hybridization (FISH) on metaphase spreads to be mosaic (46,XY/47,XXY), and 140 patients showed only 47,XXY. Small testes were observed in 95% of patients and gynaecomastia was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 24 publications
0
33
0
1
Order By: Relevance
“…Approximately one of 1,000 male newborns has the 47, XXY Klinefelter syndrome, which is one of the most common sex chromosome anomalies in azoospermic Japanese men; its prevalence is 7.4% [1]. Several reports have described successful pregnancy outcomes in these patients using fresh testicular sperm obtained on the day of oocyte retrieval [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately one of 1,000 male newborns has the 47, XXY Klinefelter syndrome, which is one of the most common sex chromosome anomalies in azoospermic Japanese men; its prevalence is 7.4% [1]. Several reports have described successful pregnancy outcomes in these patients using fresh testicular sperm obtained on the day of oocyte retrieval [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that men with KS also have higher rates of sex chromosomal aneuploidy ranging from 0.1 to 50% and autosomal aneuploidy (of chromosomes 13, 18 and 21) in their sperm compared with normal fertile men (Moosani et al 1995, Martini et al 1996, Guttenbach et al 1997a, Estop et al 1998, Foresta et al 1998, Kruse et al 1998, Aran et al 1999, Lim et al 1999, Okada et al 1999, Rives et al 2000, Hennebicq et al 2001, Levron et al 2001, Morel et al 2003, Simpson et al, 2003, an observation paralleled by studies in 41,XXY mice (Mroz et al 1999). It is also well established that spermatogenesis in male XXY mice generally arrests prior to the onset of meiosis (Lue et al 2001).…”
Section: Introductionmentioning
confidence: 92%
“…23 In a study of 148 Klinefelter's syndrome cases Okada H et al found only 12.4% subjects had gynaecomastia. 20 Tarnekar et al not reported gynaecomastia in cases of Klinefelter's syndrome. 12 This finding is similar to that of present study as gynaecomastia was absent in all the 3 cases of Klinefelter's syndrome.…”
Section: 11mentioning
confidence: 99%